Antioxidative And Hepatoprotective Role Of Cichorium Intybus And Silybum Marianum Extracts In Hepatocellular Damage (Journal of Pharmaceutical Negative Results, 2023)
Abstract: Cichorium intybus and Silybum marianum have therapeutic role in hepatocellular damage in oxidative stress. They play important role to protect hepatic cell in liver injury and normal the serum level of liver enzymes.Aims and Objectives: In this the function of liver and evaluate the liver serum enzyme levels in induced liver injury of rabbits and see the effect of Cichorium intybus and Silybum marianum plants extractsMethodology: Ethanol extracts are prepared of Cichorium intybus and Silybum marianum separately. Liver of rabbits are damaged with CCl4. The elevated values of liver enzymes (ALT, AST, ALP, Total protein, Albumin and Bilirubin). .Results: Cichorium intybus and Silybum marianum decreased the elevated levels of damaged liver enzymes. Silybum marianum has more potential than Cichorium intybus. The combine effect of both plants is more than individual plants.